Katalog der primären Hymenopteren-Typen des DEI (unter Ausschluss der Symphyta und Sphecidae s. l.). - Taeger, Andreas; Gaedike, Hannelore; Blank, Stephan M. (Contributions to Entomology = Beiträge zur Entomologie, 2005)
The primary types of 1005 Hymenoptera taxa of the collection of the DEI are listed. The reference to the original description and the type data given there are quoted. Data for the material in the collection which differ from that in the description are specified.